Phylogeny and diversification history of the large Neotropical genus Philodendron (Araceae): Accelerated speciation in a lineage dominated by epiphytes. Issue 6 (11th July 2018) - Canal, Dubán; Köster, Nils; Jones, Katy E.; Korotkova, Nadja; Croat, Thomas B.; Borsch, Thomas
Abstract : Premise of the Study: Philodendron is a large genus of 560 species and among the most conspicuous epiphytic components of Neotropical forests, yet its phylogenetic relationships, timing of divergence, and diversification history have remained unclear. We present a comprehensive phylogenetic study for Philodendron and investigate its diversification, including divergence‐time estimates and diversification rate shift analyses. Methods: We performed the largest phylogenetic reconstruction for Philodendron to date, including 125 taxa with a combined dataset of three plastid regions ( petD, rpl16, and trnK/matK ). We estimated divergence times using Bayesian evolutionary analysis sampling trees and inferred shifts in diversification rates using Bayesian analysis of macroevolutionary mixtures. Key Results: We found that Philodendron, its three subgenera, and the closely related genus Adelonema are monophyletic. Within Philodendron subgenus Philodendron, 12 statistically well‐supported clades are recognized. The genus Philodendron originated 25 mya and a diversification rate upshift was detected at the origin of subgenus Philodendron 12 mya. Conclusions: Philodendron is a species‐rich Neotropical lineage that diverged from Adelonema during the late Oligocene. Within Philodendron, the three subgenera currently accepted are recovered in two lineages: one contains the subgenera Meconostigma and Pteromischum and the other contains subgenus Philodendron . The lineage containing subgenera Meconostigma and Pteromischum underwent a consistent diversification rate. By contrast, a diversification rate upshift occurred within subgenus Philodendron 12 mya. This diversification rate upshift is associated with the species radiation of the most speciose subgenus within Philodendron . The sections accepted within subgenus Philodendron are not congruent with the clades recovered. Instead, the clades are geographically defined.